Factors influencing decline in quality of life in smokers without airflow obstruction: The COPDGene study. (January 2020) - Parekh, Trisha M.; Bhatia, Smita; Cherrington, Andrea; Kim, Young-il; Lambert, Allison; Iyer, Anand; Regan, Elizabeth A.; DeMeo, Dawn L.; Han, MeiLan; Dransfield, Mark T.
Abstract: Introduction: Current and former smokers with normal spirometry and with Preserved Ratio Impaired Spirometry (PRISm) experience respiratory events similar to chronic obstructive pulmonary disease (COPD) exacerbations. Exacerbations significantly reduce quality of life (QoL) in COPD patients however the effect of respiratory exacerbations on QoL in these groups is unknown. We hypothesized that exacerbations and change in exacerbation status would predict QoL decline among normal spirometry and PRISm participants in COPDGene. Methods: COPDGene is a multicenter, longitudinal study in the U.S. designed to identify genetic determinants of COPD. We enrolled study subjects in Phase 1 of COPDGene and performed multivariable logistic regression models to determine independent predictors of decline in quality of life [>4 points on the St George's Respiratory Questionnaire (SGRQ)]. Separate analyses were performed for current and former smokers with normal spirometry and PRISm. Frequent exacerbator status was defined by > 2 moderate or >1 severe exacerbations in the year prior to the baseline and year 5 follow-up visits. Results: Independent predictors of QoL deterioration included current smoking, higher exacerbation frequency, and a change from infrequent to frequent exacerbation status (REF: infrequent to infrequent exacerbation status) in both groups [PRISm (OR = 3.15, 95%CI, 1.67–5.94), normal spirometry (OR = 4.72, 95%CI, 3.25–6.86)]. A change from frequent to infrequent exacerbation status did not lower the odds of QoL decline in either cohort. Conclusion: Continued smoking and the onset of frequent exacerbations were predictors of QoL decline in smokers with normal spirometry and PRISm. Further studies are needed to identify modifiable factors associated with decline in QoL in smokers. Highlights: Smokers without airflow obstruction experience respiratory symptoms and acute exacerbations prompting treatment. Frequent exacerbation status is associated with quality of life decline. Stabilization of exacerbation status does not lower the odds of quality of life decline.